Russia-super power in the Black Sea: From strategic and economic aspects - Demirel, Nuri (Journal of Management, Economics, and Industrial Organization, 2018)
The Black Sea region occupies an important place in history, because of its geographical, historical, geopolitical, geostrategic, geo-economic and geo-ethnic location. Great Powers have been and continue to be of interest to it. The growing energy needs of the world and the availability of energy reserves in the Black Sea aroused the interest of the great powers. This interest will be caused by the distribution of energy resources in the future, which will become one of the reasons for the Third World War. In a global world where technology is developing at a rapid pace, as a result, in the Black Sea region, as well as in the weakest forces, intelligent games are being thought of in the world where chess pieces will be rearranged. With the end of the Cold War period, the effect of Russia declined in the Black Sea region, but with the Crimea’s accession to Russia on March 17, 2014, the balances in the Black Sea changed again in favor of Russia. This article will examine the Black Sea region and its importance, the situation in the Black Sea before and after the cold war period, Russia’s position in the Black Sea, new strategies and reactions that are changing in the Black Sea region, after the Crimea joined Russia, Russian-Ukrainian relations affecting region, Turkish-Russian relations, as well as Russia’s relations with the European Union (EU) and with NATO (North Atlantic Treaty Organization, North Atlantic Treaty Organization).